A role for fimbriae in Porphyromonas gingivalis invasion of oral epithelial cells - Njoroge, T; Genco, R J; Sojar, H T; Hamada, N; Genco, C A (Infection and immunity, 1997)
Isogenic mutants of Porphyromonas gingivalis which differ in the expression of fimbriae were used to examine the contribution of fimbriae in invasion of a human oral epithelial cell line (KB). At a multiplicity of infection of 100, the wild-type P. gingivalis strains 33277, 381, and A7436 exhibited adherence efficiencies of 5.5, 0.11, and 5.0%, respectively, and invasion efficiencies of 0.15, 0.03, and 0.10%, respectively. However, adherence to and invasion of KB cells was not detected with the P. gingivalis fimA mutants, DPG3 and MPG1. Adherence of P. gingivalis wild-type strains to KB cells was completely inhibited by the addition of hyperimmune sera raised to the major fimbriae. Examination by electron microscopy of invasion of epithelial cells by the P. gingivalis wild-type strain 381 revealed microvillus-like extensions around adherent bacteria; this was not observed with P. gingivalis fim mutants. Taken together, these results indicate that the P. gingivalis major fimbriae are required for adherence to and invasion of oral epithelial cells.